IMPLEMENTASI SENSOR KAMERA CMUCAM3 PADA MOBILE ROBOT LINE TRACER - Goegoes Dwi N; M. Aziz Muslim; Mr. Poerwanto; M. Yusuf Z (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2011)
The use of the camera sensor to identify a particular object is still a popular tool to date. In this study implemented the use of CMU cam3 camera sensors to recognize line objects as mobile robot path trajectory. From the trial which is obtained fairly good results even if the robot is still a failure that is out of the path that was set at 10:1 it means ten times the trial once the robot has an failur. Keywords—CMU cam3 Camera Sensor, mobile robot